The effects of feeder design and changing the availability of water from a wet-dry feeder at 4 and 8 weeks prior to marketing on growth performance and carcass characteristics of growing-finishing pigs - Bergstrom, J.R.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,296 pigs (PIC, 337 × 1050) were used to evaluate the effects on growth performance and carcass characteristics of feeder design (conventional dry feeder vs. wet-dry feeder) and changing availability of water from a wet-dry feeder at 4 and 8 wk prior to marketing. There were 27 pigs per pen (14 barrows and 13 gilts) and 24 pens per feeder-type. Pigs were fed identical corn-soybean meal diets with 15% dried distillers’ grains with solubles (DDGS). Pens with a wet-dry feeder had a separate cup waterer, but the feeder provided the sole water source until d 69. The water supply to the wet-dry feeder was shut off in 8 pens on d 69 (WD8) and another 8 pens on d 97 (WD4), and the cup waterer was turned on. For the remaining 8 pens, the wet-dry feeder provided the sole water source for the entire experiment (WD0). From d 0 to 69, pigs using the wet-dry feeder had improved (P < 0.05) ADG, ADFI, F/G, and d 69 BW. Overall (d 0 to 124), pigs using WD0 had greater (P < 0.05) ADG, ADFI, final BW, and HCW than all other treatments. Pigs using WD4 had greater (P < 0.05) ADG than pigs that used a conventional dry feeder, and WD8 was intermediate. Pigs using WD4 had greater (P < 0.05) ADFI than WD8, and conventional dry was intermediate. Pigs using WD0 had poorer (P < 0.05) F/G than WD8 and conventional dry, and pigs using WD4 were intermediate. Backfat depth of pigs using WD8 was reduced (P < 0.05) compared to all other treatments, and loin depth was greater (P < 0.05) than that of pigs using a conventional dry feeder and WD4. Loin depth of pigs using WD0 was also greater (P < 0.05) than that of pigs with the conventional dry feeder. The percentage fat-free lean of pigs using WD8 was greater (P < 0.05) than WD4, and WD0, and pigs that used the conventional dry feeder were intermediate. Incomeover- feed cost was numerically greatest for pigs using WD8. In conclusion, pigs using WD0 had better growth rates than pigs using the conventional dry feeder, WD4, or WD8. Although measures of carcass leanness were improved with WD8, the reduction in growth rate observed for this treatment during the last 8 wk eliminated any net improvement in the overall growth rate from using a wet-dry feeder.
Keywords: Swine; Conventional feeder; Water; Wet-dry feeder